Maternal obesity and cesarean surgical wound infection: An evidence-based reassessment of risk - Sutardji’in, Sri; Setiowati, Dewi; Famaningrum, Widati (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Obesity during pregnancy has been associated with impaired immune response and delayed wound healing, leading to a higher risk of surgical site infection (SSI) after caesarean section (CS). Previous studies have reported that obese women undergoing CS have a 31% increased risk of developing SSI. Purpose: To analyze the correlation between maternal obesity and the incidence of SSI following CS deliveries. Method: This observational analytic study applied a cross-sectional design and involved 100 patients who underwent CS between January and December 2024. Participants were selected using purposive sampling. Obesity was considered the independent variable, while SSI was the dependent variable. Data were collected from medical records and analyzed using Fisher’s exact test, with statistical significance set at p < 0.05. Results: Among the participants, 66% (n = 66) were classified as obese, while the majority, 95% (n = 95), did not experience SSI. The Fisher’s exact test yielded p = 0.163, which exceeded the significance threshold. These findings indicate no statistically significant association between maternal obesity and SSI following CS. Conclusion: Although the prevalence of obesity among the study participants was high, obesity was not significantly correlated with the incidence of SSI after CS. Further research is recommended to identify other contributing factors that may influence postoperative infections.